Production Engineering and Management
It is our pleasure to introduce the 8th edition of the International Conference on Production Engineering and anagement (PEM), an event that is the result of the joint effort of the OWL University of Applied Sciences and the University of Trieste. The conference has been established as an annual meeting under the Double Degree Master Program “Production Engineering and Management” by the two partner universities. This year the conference is hosted at the university campus in Lemgo, Germany. The main goal of the conference is to offer students, researchers and professionals in Germany, Italy and abroad, an opportunity to meet and exchange information, discuss experiences, specific practices and technical solutions for planning, design, and management of manufacturing and service systems and processes. As always, the conference is a platform aimed at presenting research projects, introducing young academics to the tradition of symposiums and promoting the exchange of ideas between the industry and the academy. This year’s special focus is on Supply Chain Design and Management in the context of Industry 4.0, which are currently major topics of discussion among experts and professionals. In fact, the features and problems of Industry 4.0 have been widely discussed in the last editions of the PEM conference, in which sustainability and efficiency also emerged as key factors. With the further study and development of Direct Digital Manufacturing technologies in connection with new Management Practices and Supply Chain Designs, the 8th edition of the PEM conference aims to offer new and interesting scientific contributions. The conference program includes 25 speeches organized in seven sessions. Two are specifically dedicated to “Direct Digital Manufacturing in the context of Industry 4.0”. The other sessions are covering areas of great interest and importance to the participants of the conference, which are related to the main focus: “Supply Chai n Design and Management”, “Industrial Engineering and Lean Management”, “Wood Processing Technologies and Furniture Production”, and “Management Practices and Methodologies”. The proceedings of the conference include the articles submitted and accepted after a careful double-blind refereeing process.